Regulatory Uncertainty Around New Breeding Techniques - Lassoued, Rim; Smyth, Stuart J.; Phillips, Peter W. B.; Hesseln, Hayley (Frontiers in Plant Science, 2018)
Emerging precision breeding techniques have great potential to develop new crop varieties with specific traits that can contribute to ensuring future food security in a time of increasing climate change pressures, such as disease, insects and drought. These techniques offer options for crop trait development in both private and public sector breeding programs. Yet, the success of new breeding techniques is not guaranteed at the scientific level alone, but political influences and social norms significantly contribute to how it will perform in the market and society. Using survey data, we report results from an international panel of experts regarding the institutional and social barriers that might impede the development of new plant technologies. Survey results clearly indicate that regulatory issues, social and environmental concerns are critical to the success of precision breeding. The cross-regional analysis shows heterogeneity between Europeans and North Americans, in particular, regarding political attitudes and social perceptions of targeted breeding techniques.